The Relationship Between Spinal Curvature Angle on Radiography and Pulmonary Function Impairment in Scoliosis Patients : A Systematic Review - Mekko Pebin; Desi Megafini; Cecep Kurnia Suhayat; Selvaning Oktania (International Medical Journal Corp. Ltd, 2026)
Introduction: Scoliosis is a three-dimensional spinal deformity that may impair pulmonary function through mechanical restriction of thoracic volume. The precise relationship between radiographic curvature magnitude and pulmonary impairment remains debated, particularly regarding whether surgical correction reliably improves lung function. Methods: This systematic review synthesised 80 studies examining the relationship between spinal curvature measurements (primarily Cobb angle) and pulmonary function tests (spirometry, lung volumes) in scoliosis patients. Studies included idiopathic, congenital, and neuromuscular aetiologies, with sample sizes ranging from 11 to 8,723 patients. Key outcomes were correlation coefficients, effect sizes, and changes in percent-predicted FVC and FEV1. Results: A significant inverse linear relationship exists between thoracic Cobb angle and pulmonary function in untreated idiopathic scoliosis. Kempen et al. (2021) demonstrated a decrease of approximately 1% predicted pulmonary function per 2.6–4.5 degrees of scoliosis (p<0.001). Kan et al. (2022) confirmed significant negative correlations: %FVC (r=−0.302), %FEV1 (r=−0.348), and %TLC (r=−0.183), all p<0.001. Thoracic kyphosis showed a positive correlation with %FVC (r=+0.180, p<0.05), indicating hypokyphosis independently worsens restriction. Surgical correction significantly improves percent-predicted FVC only in severe curves (>100°), with Grabala et al. (2023) reporting improvement from 51.2% to 69.9% (p<0.001). In moderate curves (50°–70°), Burgos et al. (2025) found no significant change in %FVC at 10+ years follow-up (MD −2.90, 95% CI −5.98 to 0.18). Posterior-only approaches preserve function better than thoracotomy or thoracoplasty. Preoperative halo-pelvic traction improved FVC by 15.6% (p=0.024). In Duchenne muscular dystrophy, surgery reduced FVC decline from 7.80%/year to 4.26%/year (p<0.001). Baseline FVC% was the strongest predictor of postoperative pulmonary complications (OR=0.91 per unit increase, p=0.013). Discussion: The curvature-PF relationship is real but explains only 5–8% of variance in pulmonary impairment. The apparent paradox of significant correlation without consistent surgical improvement is reconciled by threshold effects (only severe curves benefit), surgical approach (chest wall violation negates benefits), and growth confounding. Three-dimensional deformity parameters (apical rotation, kyphosis, rib anomalies) independently predict PF beyond coronal Cobb angle. Conclusion: Thoracic Cobb angle demonstrates a significant negative correlation with pulmonary function in untreated scoliosis, with approximately 1% FVC loss per 3–4 degrees of curvature. However, surgical correction reliably improves percent-predicted pulmonary function only in patients with severe deformity (>100°) and baseline impairment. For moderate idiopathic curves, posterior-only fusion preserves rather than improves function. Neuromuscular scoliosis surgery attenuates decline rather than achieving improvement. Preoperative pulmonary function is the dominant prognostic factor across all etiologies.